2004
DOI: 10.1029/2003ja010019
|View full text |Cite
|
Sign up to set email alerts
|

Schumann resonance frequency increase during solar X‐ray bursts

Abstract: [1] Variations of the first mode Schumann resonance frequency in the Kola Peninsula and of the first and second mode frequencies in Kamchatka during seven days of MarchApril 2001, when the intensive solar X-ray bursts occurred, are studied with 5 min averaging. All X-ray bursts were accompanied by $0.2 Hz increase in the first mode frequency, at least in one of the magnetic components. Duration of the increases coincided with that of the bursts. For the second mode the increase (in average by $0.3 Hz) was regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 13 publications
(20 reference statements)
4
29
0
Order By: Relevance
“…During the solar proton events (SPE), high-energy particle precipitation is often accompanied by X-ray bursts leading to significant perturbations of the conductivity in the cavity. Different shifts of the SR parameters were reported in the realistic measurements [e.g., Schlegel and Füllekrug, 1999;Roldugin et al, 2001Roldugin et al, , 2003Roldugin et al, , 2004aSátori et al, 2005]. In our previous work [Yang and Pasko, 2005], the variation patterns of the first SR frequency associated with the ionospheric conductivity perturbation during SPEs and X-ray bursts were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…During the solar proton events (SPE), high-energy particle precipitation is often accompanied by X-ray bursts leading to significant perturbations of the conductivity in the cavity. Different shifts of the SR parameters were reported in the realistic measurements [e.g., Schlegel and Füllekrug, 1999;Roldugin et al, 2001Roldugin et al, , 2003Roldugin et al, , 2004aSátori et al, 2005]. In our previous work [Yang and Pasko, 2005], the variation patterns of the first SR frequency associated with the ionospheric conductivity perturbation during SPEs and X-ray bursts were discussed.…”
Section: Introductionmentioning
confidence: 99%
“…The solar proton event is modeled as azimuthally symmetric conductivity perturbations at an altitude of 40 km and centered at the North and South Poles; the X-ray burst is modeled as an azimuthally symmetric conductivity perturbation at an altitude of 70 km and centered only at the North Pole. A discussion follows comparing the FDTD-calculated results with previous reports in the literature [56], [60]- [63].…”
Section: Schumann Resonancesmentioning
confidence: 99%
“…Schumann resonance frequencies determined separately for N-S and E-W magnetic component differ by 0.5-1.8 Hz (Sentman, 1987(Sentman, , 1989. The variation in first and second mode Schumann resonance frequency occurred during the intense solar X-ray burst by ∼0.2 Hz and 0.3 Hz, respectively (Roldugin et al, 2004b). Hayakawa et al (2008) showed the short term spectral modification associated with the Moshiri (Japan) earthquake, in the Schumann resonance frequency band of 2.5-40 Hz.…”
Section: R Chand Et Al: Schumann Resonance Frequency Variations Obsmentioning
confidence: 99%